BRAZIL AND THE REGIONAL LEADERSHIP VACUUM: THE CHINESE-AMERICAN ADVANCE (2011/2016) - do Carmo, Corival Alves; Pecequilo, Cristina Soreanu (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The first decade of the 21st century was characterized by Brazil’s action in South America. However, since 2011, there was a setback in the country´s strategic, economic and political investments in integration, allowing the projection of the US and China. The aim of this article is to analyze this context.